2019
DOI: 10.1186/s12879-019-3699-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the molecular epidemiology of Staphylococcus aureus across and within fitness facility types

Abstract: BackgroundStaphylococcus aureus is a common bacterium found in the nose and throat of healthy individuals, and presents risk factors for infection and death. We investigated environmental contamination of fitness facilities with S. aureus in order to determine molecular types and antibiotic susceptibility profiles of contaminates that may be transmitted to facility patrons.MethodsEnvironmental swabs (n = 288) were obtained from several fitness facilities (n = 16) across Northeast Ohio including cross-fit type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
(51 reference statements)
1
9
2
2
Order By: Relevance
“…The results supported the hypothesis that fitness center equipment were host to an abundance of WHO priority pathogens. While previous studies reported fomite bacterial loads of up to 20 to 50 million CFU/mL (Chitturi and Lakshmi, 2018;Dalman, et al, 2019), this study yielded much a higher range (7.6 x 10 9 -1.0 x 10 13 CFU/mL, mean: 2.5 x 10 12 CFU/mL) of bacterial abundance. Additionally, at least one (and up to three) antibiotic resistant WHO pathogens were identified from each equipment sampled (Table 2).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The results supported the hypothesis that fitness center equipment were host to an abundance of WHO priority pathogens. While previous studies reported fomite bacterial loads of up to 20 to 50 million CFU/mL (Chitturi and Lakshmi, 2018;Dalman, et al, 2019), this study yielded much a higher range (7.6 x 10 9 -1.0 x 10 13 CFU/mL, mean: 2.5 x 10 12 CFU/mL) of bacterial abundance. Additionally, at least one (and up to three) antibiotic resistant WHO pathogens were identified from each equipment sampled (Table 2).…”
Section: Discussioncontrasting
confidence: 64%
“…Bacterial load, presence of pathogenic bacteria, and abundance of pathogenic and antibiotic resistant strains was determined via serial dilutions and plate counts, selective screening with specialized growth media, colony isolation, and biochemical tests using API ® 20E chemical panels (bioMerieux, VWRTM, Radnor, PA), respectively. The most notable results of this study were bacterial loads much higher than what has been found in previous studies (Goldhammer et al, 2006;Ryan et al, 2011;Mukherjee et al, 2014;Ibrahim et al, 2018;Dalman et al, 2019;Fadare, 2019) and 100 percent of fomites testing positive for Methicillin-resistant Staphylococcus aureus (MRSA).…”
Section: Fomites In the Fitness Center: Fitness Equipment Harbors Antibiotic Resistant And Pathogenic Bacteriacontrasting
confidence: 59%
“…This prevalence is even higher than that reported in 2013 from the neighboring Nairobi region, although the earlier study analyzed isolates from patients with specific conditions [ 16 ]. However, the prevalence is lower than the 56.8% reported in Nepal [ 41 ], 57.1% in Gambia [ 1 ], and 73% in Uganda [ 40 ]. In our analysis, we have observed a significant association between MRSA and PVL with 9 out of the 14 (64%; 95% CI = 0.35–0.87) PVL positive isolates also being MRSA.…”
Section: Discussionmentioning
confidence: 75%
“…The main source of bacteria present on the surface of fitness facilities is people who come to exercise (Ramos et al 2014). Dalman et al (2019) found 38.2% of the environmental surfaces in 16 fitness facilities in Northeast Ohio in the USA were contaminated with Staphylococcus aureus, a common gram-positive bacterium species found in the nose and throat of humans. On the other hand, most fungal sources are located outdoors, e.g., soil, plants, and water bodies.…”
Section: Introductionmentioning
confidence: 99%